Thermal Modelling and Analysis of A 10HP Induction Machine Using the Lumped Parameter Approach - Oti, Stephen Ejiofor; Awah, Chukwuemeka; Chibuzo, Nnonyelu; Okoro, Ogbonnaya (International Journal of Integrated Engineering, 2021)
The essence of this research work is to develop a thermal model for an induction machine that will enable the prediction of temperature in different parts of the machine. This is very important first to the manufacturer or designer of an induction machine because with these predictions one can decide on the insulation class limits the machine belongs to. Also modern trends in the construction of machines is moving in the direction of making machines with reduced weights, costs and increased efficiency. In order to achieve this, the thermal analysis becomes very crucial in deciding on what types of insulators and other materials that would be used to make these machines. In industries, the knowledge of the thermal limits of machines if well utilized increases the life span of the machines and reduces downtime; thereby increasing production and profit. Specifically, this paper (i) predicted the temperature limits of the induction machine and its components, (ii) developed an accurate thermal model for an induction machine, (iii) predicted the temperature in different parts of the induction machine using the thermal model and software program and lastly (iv) investigated how the machine symmetry is affected by the nodal configuration.